Am I worth it? Gifting myself with luxury. Issue 2 (2014) - ,; ,; ,; ,; ,; ,; ,
Abstract : Purpose – Consumers gift themselves with luxury fashion brands, yet the motives for self‐gifting are not well understood. Whereas traditionally, self‐gifting is defined as self‐orientated in nature, luxury brands are seen as social statements, and self‐gifting of luxury fashion brands that combine these two controversial areas is an interesting research topic. The purpose of this paper is to address this issue by exploring the self‐gifting behaviour of consumers, in particular focusing on the personal motives of gifting oneself with luxury fashion brands.Design/methodology/approach – The study takes a multi‐qualitative approach involving a small ( n =19) but rich sample. Data collection and analysis were triangulated to reduce researcher biases.Findings – The study provides key dimensions for understanding consumers' perceptions of luxury fashion brands and self‐gifting motives (self and socially orientated). The findings reveal that reflections from others are part of the self‐gifting phenomenon. It appeared that although self‐orientated benefits and personally orientated motives trigger the self‐gifting act, the act of actually purchasing explicitly luxury brands for oneself as a gift may be triggered by other‐orientated benefits and socially orientated motives. The findings also imply that luxury holds a self‐orientated aspect; luxury brands are not only purchased for socially orientated reasons but also for reasons related to oneself. In addition, the findings discuss the act of shopping, where the act can be perceived as a luxury experience and overrun the importance of the brand.Practical implications – The findings provide insights to consumers' gifting behaviour that may be valuable for retailers and fashion marketers as they plan for marketing activities related to their customers' self‐gifting.Originality/value – Self‐gifting represents a view of gifting that remains under‐researched. This study uncovers the motives for gifting oneself with luxury fashion brands, a further sub‐area in need for more investigation.